A long way to walk: Bus Boycotts in Alexandra, 1940-1945 - Stadler, Alfred William (My University, 1979)
Bus boycotts assumed central significance in the political struggles in urban areas during the forties and fifties. The Alexandra boycott of 1957, which evoked sympathy boycotts across the country, even in areas in which bus fares had not been increased, reached the proportions of a major confrontation between the state on the one hand and African communities and political organisations on the other.
African Studies Seminar series. Paper presented April 1979
Keywords: Boycotts. South Africa; Transportation. South Africa; Buses. South Africa